Sternal osteomyelitis after bacillus Calmette-Guérin vaccination - Rolandas Selvestravičius; Elena Sučilienė; Kęstutis Saniukas; Odeta Bobelytė; Vytautas Usonis (MDPI AG, 2016)
Presented here is the case of a nine-month-old boy with the osteomyelitis of the upper area sternum caused by bacillus Calmette-Guerin (BCG), the Danish 1331 strain vaccine against tuberculosis. Upon examination, a swelling of approximately 2×3 cm diameter was observed in the upper sternal area. The mass was hard, fixed and sensitive to palpation with no local skin hyperaemia. Chest X-rays revealed a round mass anterior to the sternum, suggesting a diagnosis of osteomyelitis. A consequent sternal biopsy was performed and Mycobacterium bovis BCG was identified by a positive growth culture.